1731. Rezafungin Activity against Candida spp. and Aspergillus spp. Isolates Causing Invasive Infections Worldwide in 2021. (15th December 2022) - Carvalhaes, Cecilia G; Rhomberg, Paul; Rhomberg, Paul; Strand, Greg; Klauer, Abby L; Castanheira, Mariana
Abstract: Background: Rezafungin (RZF) is a once-weekly echinocandin (ECH) with a long half-life and front-loaded drug exposure. RZF is in development to treat candidemia and invasive candidiasis and prevent invasive fungal disease caused by Candida, Aspergillus, and Pneumocystis spp. We evaluated the in vitro activity of RZF, caspofungin (CSF), micafungin (MCF), and anidulafungin (ANF) against a worldwide collection of fungal isolates causing invasive infection. Methods: 830 isolates were collected from Europe (EU; 40.2%), North America (NA; 31.6%), Asia-Pacific (APAC; 15.3%), and Latin America (LA; 12.9%), identified by MALDI-TOF and/or sequencing, and tested by CLSI broth microdilution. Isolates included C. albicans (CA; 316 isolates), C. glabrata (CG; 162), C. parapsilosis (CP; 148), C. tropicalis (CT; 83), C. dubliniensis (CD; 21), C. krusei (CK; 19), Cryptococcus neoformans (CN; 10) A. fumigatus (AF; 59), and A . section Flavi (ASF; 12). CLSI criteria was applied, including the recently approved rezafungin provisional breakpoints against Candida spp. Results: RFZ inhibited 99.7% of CA, 98.1% of CG, 95.2% of CD, and all CP, CT, and CK (MIC50/90 in Table) at the susceptibility (S) breakpoint (BP). RZF had similar activity to the other ECHs against CA (99.7%S), CG (95.7-96.3%S), CT (100.0%S), CK (100.0%S), and CD (MIC50/90 range, 0.015-0.06/0.03-0.06 mg/L). Although CSF displayed lower MIC50/90 values (0.25/0.25 mg/L) than RZF (MIC50/90, 1/2 mg/L), MCF (MIC50/90, 1/1 mg/L), and ANF (MIC50/90, 2/4 mg/L) against CP, all ECHs but ANF (87.2%S) inhibited 100% of CP isolates at the respective BP. Only 1 CA (EU), 1 CD (EU), and 3 CG (NA) were non-S to RZF, while 1 CA (EU), 6 CG (5 NA, 1 APAC), and 19 CP (8 EU, 5 NA, 4 APAC, 2 LA) were ANF non-S. Limited activity was noted for all ECHs against CN (MIC50, > 4 mg/L). All AF isolates were inhibited by RZF at ≤ 0.06 mg/L, and ANF, MCF, and CSF at ≤ 0.12 mg/L. RZF (MIC range, 0.008-0.06 mg/L) and other ECHs (MIC range, 0.008-0.12 mg/L) were also active against 7 voriconazole non-S AF isolates (4 NA, 3 EU). RZF and other ECHs inhibited all ASF isolates at ≤ 0.06 mg/L. Conclusion: RZF was very active against Candida spp., AF, and ASF isolates causing invasive infections worldwide, including voriconazole non-S AF isolates and CP displaying non-S to ANF. Disclosures: Cecilia G. Carvalhaes, MD, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|Melinta: Grant/Research Support|Pfizer: Grant/Research Support Paul Rhomberg, BS, MT(ASCP), Cidara: Grant/Research Support|Pfizer: Grant/Research Support Paul Rhomberg, BS, MT(ASCP), Cidara: Grant/Research Support|Pfizer: Grant/Research Support Greg Strand, MLS (ASCP)CM, Cidara: Grant/Research Support Abby L. Klauer, BS, Cidara: Grant/Research Support Mariana Castanheira, PhD, AbbVie: Grant/Research Support|Cidara: Grant/Research Support|GSK: Grant/Research Support|Melinta: Grant/Research Support|Pfizer: Grant/Research Support|Shionogi: Grant/Research Support.